Factors influencing implementation of mass drug administration for lymphatic filariasis elimination: a mixed-method study in Odisha, India - Ratna, P.; Sinha, Abhinav; Pati, Sanghamitra; Sahoo, Prakash Kumar (Frontiers in Pharmacology, 2024)
Lymphatic filariasis (LF) persists as a public health problem in India. Despite more than ten rounds of MDA, LF continues to be endemic in Dhenkanal district of Odisha. Hence, we assessed the coverage and compliance of MDA program and explored the factors affecting it in Dhenkanal district.An explanatory mixed-method study was conducted wherein for the quantitative survey, 552 participants aged two years and above were recruited following multistage cluster random sampling during February 2022. In-depth interviews were conducted among purposively selected key stakeholders, and programme implementers. Descriptive statistics were used to report coverage and compliance along with 95% confidence interval. Qualitative data were analyzed using thematic approach.We observed a coverage of 99.28% and compliance of 85.87% for MDA drugs. Supervised drug administration proved was the major pillar in increasing compliance. There was a difficulty in administering drugs in the urban areas due to gated societies, absence of individuals during the day, and perspective towards healthcare providers. Participants reported lack of confidence on drug distributors, and fear of side effects as major cause for non-compliance.There is a need to strengthen MDA especially in urban areas. Urban specific strategy along with surveillance, behavioral change communication and involvement of multi-disciplinary teams is required.